Analisis Pengaruh Quick Ratio (QR), Debt to Equity Ratio (DER), dan Return on Equity (ROE), Terhadap Nilai Perusahaan (PER) Pada Perusahaan Sub Sektor Iron & Steel Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Fatimatul Khairunnisa; Dedi Nur Fadjri; Marsela Oktafia Ramadani; Muhamad Nur Arif; Bambang Hermawan (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the influence of the Quick Ratio (QR), Debt to Equity Ratio (DER), and Return on Equity (ROE) on firm value—proxied by the Price-Earnings Ratio (PER)—in iron and steel sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative method with an associative approach was employed, utilizing secondary data from the financial statements of iron and steel sub-sector companies for the 2020–2024 period. The sample was selected using purposive sampling, resulting in 9 companies and a total of 45 observations, which were analyzed via panel data regression using EViews software. The results indicate that QR, DER, and ROE—both simultaneously and partially—have a significant effect on firm value. The novelty of this study lies in its use of a combination of liquidity, capital structure, and profitability variables within the iron and steel sub-sector, covering the most recent period.